Trichostrongylus and Haemonchus anthelmintic resistance in naturally infected sheep from southern Brazil - KLAUCK,VANDERLEI (2014)
The anthelmintic resistance in small ruminants is a common problem and concern worldwide. The aim of this study was to verify anthelmintic treatment efficacy in naturally infected sheep. This study was conducted on nine herds that used the same anthelmintic management for over a year. In each farm, the animals were divided into two groups: untreated control group (n = 5) and treated (n = 10) according to the number of eggs per gram of feces (EPG). The treatment effect was checked based on EPG results and larval culture performed before treatment and 10 days after treatment. Significant differences were not observed (P> 0.05) on EPG results between untreated and treated groups. The coproculture showed that the animals were infected primarily byHaemonchus spp., Trichostrongylus spp.,Teladorsagia spp., Cooperia spp. andOesophagostomum spp. In all farms, anthelmintic resistance by genera Haemonchus and Trichostrongylus was found, but this resistance varied greatly between farms.Haemonchus spp. showed resistance to closantel, levamisole, and albendazole. Trichostrongylus spp. was shown to be resistant to closantel, levamisole, and albendazole. The drugs tested showed to be efficient against the genera Teladorsagia,Cooperia, and Oesophagostomum. Based on these results, we conclude that the anthelmintic resistance to the tested drugs is a problem present in the farms evaluated.